Development of training materials - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Development of training materials in agriculture: a course manual by Anthony Youdeowei and Joseph Kwarteng 1995 104pp ISBN 92 9113 0729